APPLICATION OF ERGONOMICS IN COMPUTERIZED WORKS: A CASE STUDY (Fiep Bulletin - online, 2016)
This research was carried out with 2 working females (?) the administrative sector in age from 25 to 27 years, with service time ? 3 years of a company in western Paraná, Brazil. The objective was to assess the ergonomic risks in Human Computer Interaction. The percentage of body discomfort through the diagram of Corlet and job by RULA (Rapid Upper Limb Assment) was observed. The statistics were performed using 5.0 Bioestatic program. The data of the discomforts showed that the region of the shoulders, spine, knees and feet, have values ??greater than 67%, and in the cervical spine and shoulders 100%. We conclude that the jobs analyzed, are ergonomically inadequate, which may provide the appearance of lesions in workers, ergonomics correction is necessary so that employees can develop your tasks with comfort, health and safety.
Keywords: computer; ergonomics; human